Feasibility Analysis of Lightning Grounding System at SAMSAT Soekarno-Hatta Building Bandung City Based on PUIL Standard - Mochmamad Raihan Febriana; Linda Faridah (Journal of Mechatronics and Artificial Intelligence, 2024)
Protection from surges caused by lightning is an important concern in public buildings, including in SAMSAT Soekarno-Hatta Building, Bandung City, which functions as a service center with high electricity consumption and various sensitive electronic equipment. An adequate grounding system is required to conduct excess current to ground to protect electronic devices and ensure occupant safety. This study aims to evaluate the feasibility of the lightning grounding system at the Bandung SAMSAT Building based on the PUIL 2000 safety standard, which stipulates that the grounding resistance value must be below 5 ohms to achieve optimal protection. The grounding resistance measurement is carried out using an earth tester, which is able to measure the actual resistance of the building grounding system. Based on the measurement results, the resistance value obtained is 4.44 ohms. This value meets the requirements of PUIL 2000 and indicates that the grounding system in the building is within safe limits. In addition to resistance measurements, visual observations were also made to ensure the physical condition of grounding components, such as lightning rods and connecting conductors, which were found to be in good condition although there were signs of light corrosion on the conductors. The conclusion of this research shows that the grounding system in the Soekarno-Hatta SAMSAT Building meets the eligibility standards for lightning protection. This has positive implications for the protection of buildings and electronic equipment from the risk of lightning strikes. The suggested recommendation is routine maintenance to maintain the performance of the grounding system, especially in the area of corroded conductors, so that the resistance value remains within safe limits.